Comparison of the antibacterial efficacies of ampicillin and ciprofloxacin against experimental infections with Listeria monocytogenes in hydrocortisone-treated mice. - van Ogtrop, M L (1992)
The efficacies of ciprofloxacin and ampicillin against Listeria monocytogenes in an immunosuppressed mouse model of listeriosis were compared. Immunosuppression was achieved by administration of 2.5 mg of hydrocortisone acetate daily. Both ciprofloxacin and ampicillin were effective in reducing the number of viable L. monocytogenes cells in the liver and spleen. After treatment with 100 mg of ampicillin per kg of body weight every 6 h for 3 days, virtually no L. monocytogenes could be recovered from the livers and spleens of the mice. In contrast, after treatment with 100 mg of ciprofloxacin per kg every 6 h for 3 days, a geometric mean of 5 x 10(4) CFU of L. monocytogenes was recovered from the spleens and 1 x 10(5) CFU was recovered from the livers of the mice. Results of the study show that the antibacterial efficacy of ampicillin is far superior to that of ciprofloxacin in our animal model of listeriosis.